Balancing Conscience: A Response to Fernandes & Ecret - Wolfe, Ian; Guiahi, Maryam (Conatus - Journal of Philosophy, 2020)
There are many lessons that bioethics can learn from the Holocaust. Forefront are the lessons from the Nuremberg trials and the formation of research ethics. An often-overlooked lesson is how the Nazi regime was able to construct a hierarchy in such a way that influenced people to act in horrendous ways. Fernandes & Ecret, writing in Conatus – Journal of Philosophy 4, no. 2 (2019), highlight the influence of hierarchy on the moral silence of nurses and physicians within the Nazi regime. While we greatly enjoyed the paper, and think it is an important contribution, we find several misrepresentations of current bioethical discourse. There is not a global acceptance of euthanasia or medical aid in dying, the contemporary position in bioethics does not favor removal of conscience-based protections, and the lack of personal conscience-based protections was not the main factor in the analysis of Nazi medical hierarchy. The authors’ overall conclusion that their analysis suggests the importance of strengthening personal conscience-based objections to prevent medical hierarchy from influencing immoral behavior misses the more significant issue of institutional behavior. Instead, we argue, that the lessons from the analysis of Nazi nurses and physicians speak to the importance of protecting patients from institutional conscience-based objections that violate patient rights of access to legal medical services. This paper will respond to the misrepresentations. We highlight the growing threats to health care access from religious affiliated institutions, the threats to professional ethics and physician and nurse scope of practice. We conclude that the analysis by Fernandes & Ecret does point out an important lesson, but rather than showing the importance of individual conscience protections, it speaks to the importance of protecting patient rights.